PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL - Patricia, Thania; Ekadjaja, Agustin (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to determine the effect of the independent variable firm size, profitability, liquidity and asset structure on the dependent variable capital structure. This study uses manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in the 2018-2020 period as the object of research. A sample of 102 data was obtained which was then processed with Ms. Excel and Eviews. The results of the F-test show that the value is smaller than the significant level of 5%, the F-test value shows the number 0.000000. This value proves that the variables of firm size, profitability, liquidity, and asset structure simultaneously have a significant effect on the capital structure variable. Furthermore, firm size and liquidity do not significantly affect capital structure because a firm does not really need external funding such as debt and prefers internal funding. They tend to choose other paths for the sustainability of the company. Profitability and asset structure actually have a significant positive effect on capital structure. This is because the large number of fixed assets of the company makes investors' confidence increase.